Reduced Severity of Pertussis in Persons With Age-Appropriate Pertussis Vaccination—United States, 2010–2012. (8th July 2017) - McNamara, Lucy A; Skoff, Tami; Faulkner, Amanda; Miller, Lisa; Kudish, Kathy; Kenyon, Cynthia; Bargsten, Marisa; Zansky, Shelley; Sullivan, Amy D; Martin, Stacey; Briere, Elizabeth
Summary: Analysis of US surveillance data demonstrates that both severe and clinically significant pertussis illnesses are less common among patients who have received age-appropriate vaccination for pertussis, demonstrating that the positive impact of pertussis vaccination extends beyond decreasing risk of disease. Abstract: Background: In 2012, >48000 pertussis cases were reported in the United States. Many cases occurred in vaccinated persons, showing that pertussis vaccination does not prevent all pertussis cases. However, pertussis vaccination may have an impact on disease severity. Methods: We analyzed data on probable and confirmed pertussis cases reported through Enhanced Pertussis Surveillance (Emerging Infections Program Network) between 2010 and 2012. Surveillance data were collected through physician and patient interview and vaccine registries. We assessed whether having received an age-appropriate number of pertussis vaccines (AAV) (for persons aged ≥3 months) was associated with reduced odds of posttussive vomiting, a marker of more clinically significant illness, or of severe pertussis (seizure, encephalopathy, pneumonia, and/or hospitalization). Adjusted odds ratios were calculated using multivariable logistic regression. Results: Among 9801 pertussis patients aged ≥3 months, 77.6% were AAV. AAV status was associated with a 60% reduction in odds of severe disease in children aged 7 months–6 years in multivariable logistic regression and a 30% reduction in odds of posttussive vomiting in persons aged 19 months–64 years. Conclusions: Serious pertussis symptoms and complications are less common among AAV pertussis patients, demonstrating that the positive impact of pertussis vaccination extends beyond decreasing risk of disease.